Visible‐Light‐Driven Multicomponent Radical Cascade Versatile Alkylation of Quinoxalinones Enabled by Electron Donor Acceptor Complex in Water. Issue 7 (24th March 2023) - Sun, Bin; Tang, Xiao‐Li; Zhuang, Xiaohui; Ling, Lan; Huang, Panyi; Wang, Jiayang; Jin, Can
Abstract: An operationally simple aqueous phase three‐component photochemical strategy for the alkylation of quinoxalin‐2(1 H )‐ones with diethyl α ‐bromomalonate and unactivated alkenes in the absence of both photoredox catalysts and additive has been developed. This reaction is driven by the photochemical activity of electron donor‐acceptor (EDA) complexes formed by quinoxalin‐2(1 H )‐ones and diethyl α ‐bromomalonate. Irradiation with visible light triggered single‐electron transfer (SET) from the quinoxalin‐2(1 H )‐ones to the diethyl α ‐bromomalonate, inducing the formation of the corresponding alkyl radical and the subsequent radical tandem reaction. It provides an efficient way to construct alkylated quinoxalinones from simple small molecules. Abstract :